Implementasi Program Coaching Guru Senior Untuk Meningkatkan Keterampilan Dasar Mengajar Guru-Guru Muda Di SMP Negeri 21 Kota KupangTahun Pelajaran 2023/2024 - Yosefina Hoar Klau (CV. Multi Kreasi Media, 2023)
This research aims to enhance the basic teaching skills of young teachers at Public Junior High School 21 in the city of Kupang through a senior teacher coaching program during the academic year 2023/2024. This school action research consists of three cycles: pre-cycle, Cycle I, and Cycle II. In the pre-cycle phase, the initial evaluation revealed that a significant portion of the teachers had low levels of basic skills, with only 45% being considered